2007
DOI: 10.1074/jbc.m700629200
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Cap-binding Complex and RNA Export Factor Is Required for Intronless mRNA Export

Abstract: RNA export factor (REF) is a component of the exon junction complex (EJC) that is deposited onIn eukaryotic cells, pre-mRNAs are primarily transcribed by RNA polymerase II (RNAPII); this process is followed by complex RNA processing steps that include capping, splicing, and polyadenylation to produce mature mRNAs. Recent studies have shown that individual events occurring during eukaryotic gene expression are coupled together under more elaborate regulatory controls than previously imagined (1-5). Coupling sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 58 publications
4
76
1
Order By: Relevance
“…Yra1) could bind at several sites along the mRNA. Indeed, it has shown Yra1 is associated with the nascent mRNA transcript from the 5Ј to the 3Ј part (38), and the mammalian Yra1 homologue Aly/Ref and members of the human TREX complex were found to associate with the 5Ј part of the mRNA involving the cap binding complex (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Yra1) could bind at several sites along the mRNA. Indeed, it has shown Yra1 is associated with the nascent mRNA transcript from the 5Ј to the 3Ј part (38), and the mammalian Yra1 homologue Aly/Ref and members of the human TREX complex were found to associate with the 5Ј part of the mRNA involving the cap binding complex (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…During mRNA biogenesis, the mRNA export factors are recruited via the 5' cap structure. 18,19 The mechanism to arrest export factor recruitment may It was determined that paraspeckles are sensitive to RNase treatment after cell permeabilization. 7,8 They suggested that an as-yet-unidentified RNA molecule was required for their structural maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA cap structure consists of a seven-methylguanosine moiety attached to the nascent mRNA via a 59-59 triphosphate linkage. The cap structure recruits cap-binding complex (CBC) that plays crucial roles in maintaining the stability of mRNA and its splicing, export, and translation (Izaurralde et al 1994;Colot et al 1996;Izaurralde et al 1995;Flaherty et al 1997;Schwer et al 1998;Shatkin and Manley 2000;Shen et al 2000;Ishigaki et al 2001;McKendrick et al 2001;Maquat 2004;Gornemann et al 2005;Hosoda et al 2005;Svitkin et al 2005;Balatsos et al 2006;Nojima et al 2007;Wong et al 2007;Kuhn et al 2008;Laubinger et al 2008). Further, CBC has been recently implicated in controlling transcriptional initiation and elongation, histone H2B ubiquitylation, histone H3K36 (lysine 36) methylation, RNA interference, cell proliferation, and processing of primary microRNAs (Kim et al 2008;Gruber et al 2009;Hossain et al 2009Hossain et al , 2013Nielsen et al 2009;Sabin et al 2009;Lahudkar et al 2011;Lidschreiber et al 2013).…”
mentioning
confidence: 99%